2017
DOI: 10.1002/ccd.26887
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of a biodegradable polymer Cobalt‐Chromium sirolimus‐eluting stent (EXCEL2) in treating de novo coronary artery disease: A pooled analysis of the CREDIT II and CREDIT III trials

Abstract: EXCEL2 stent met the objective performance criterion on efficacy and safety with a low level of 12-month TLF as well as stent thrombosis when treating patients with de novo coronary lesions. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
5
1
Order By: Relevance
“…Similarly, in the FLEX registry Lemos et al reported 2.2% major adverse cardiac events at 6-month follow-up with Supraflex SES 17. Furthermore, the CREDIT-III trails on the Excel 2 biodegradable polymer–coated, thin-struts (88 µm) DES reported 5% target-lesion failure and 0.1% TLR at 6 months 35. All these observations are comparable with the findings of the present registry (Table 6).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, in the FLEX registry Lemos et al reported 2.2% major adverse cardiac events at 6-month follow-up with Supraflex SES 17. Furthermore, the CREDIT-III trails on the Excel 2 biodegradable polymer–coated, thin-struts (88 µm) DES reported 5% target-lesion failure and 0.1% TLR at 6 months 35. All these observations are comparable with the findings of the present registry (Table 6).…”
Section: Discussionsupporting
confidence: 89%
“…The rate of cardiac death in the HELIOS registry was higher than that in previous studies except for the P-SEARCH registry [23–30] . Further analyses showed that the cardiac death rates in patients diagnosed with stable angina, unstable angina, NSTEMI, and STEMI were 1.2%, 0.9%, 3.7%, and 4.3%, respectively, indicating that the relatively higher incidence of cardiac death could be partly due to the high proportion of patients with AMI in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…After the procurement, ten DES brands are currently sharing 80% of the market, and the HELIOS stent is among them. In Supplementary Table 1, http://links.lww.com/CM9/B271, we enumerated the pivotal studies of the centrally purchased stents and currently most commonly used stents worldwide [23–31] . In this table, data from the largest real-world study are presented; otherwise, the results of the latest randomized controlled trial are included.…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography analysis showed rapid endothelialization after EXCROSSAL implantation in the CREDIT I trial, and 93.51% of struts were covered at the 4‐month follow‐up . We have reported the 1‐year clinical follow‐up of CREDIT II and CREDIT III trial, in which lesions are more complex than CREDIT I, here we demonstrate on the 3‐year clinical follow‐up of the EXCROSSAL stent.…”
Section: Introductionmentioning
confidence: 54%
“…In the subgroup analysis, the number of PCI target lesions, RVD, and multi‐vessel diseases had a significant impact on the prognosis, suggesting that these factors should be the focus in a future study. Additionally, lesion length had a significant effect on the incidence of TLF at 1‐year follow‐up data; however, not in the 3‐year follow‐up, which requires further clarification. Furthermore, sirolimus coating was regarded as inferior for patients with diabetes mellitus; however, no diabetic effects were found in our subgroup analysis.…”
Section: Discussionmentioning
confidence: 88%